QO‘SHMA GAPLARNI O‘QITISHGA OID METODIK TAVSIYALAR - Asrorova, Mo‘mina (FILOLOGIYA UFQLARI JURNALI, 2021)
The article presents the semantic and syntactic features of conjunctions and methodological recommendations for their teaching in the native language lesson in the 9th grade.